Combination of Navigated Macular Laser Photocoagulation and Anti-VEGF Therapy: Precise Treatment for Macular Edema under Dry Retinal Conditions - Ernest V. Boiko; Dmitrii S. Maltsev (Journal of Ophthalmology)
Purpose. To compare the controllability of navigated macular laser photocoagulation (MLP) in dry versus edematous retina and validate that pretreatment diagnostic images can be used as basis for navigated MLP after the macular edema (ME) has been resolved. Materials and Methods. Group 1 was divided into subgroup 1 (dry retina MLP) and subgroup 2 (MLP in ME) for comparisons of laser-burn diameters. In group 2, the areas and locations of ME before an intravitreal injection of anti-VEGF (IVAV) were compared with those of recurrent ME. Results. The average actual diameter as percentage of planned diameter of laser burn in subgroup 1 (11 DME eyes, 6 BRVO eyes) versus subgroup 2 (5 DME eyes, 8 BRVO eyes) was 115.1 ± 9.1% versus 167.2 ± 13.8% (based on retro-mode scanning laser ophthalmoscopy), and 118.1 ± 14.8% versus 176.1 ± 11.6% (based on OCT) (p<0.001). In group 2 (6 DME eyes, 6 BRVO eyes), difference in mean ME area before IVAV and that in recurrent edema was insignificant (p>0.05). Conclusion. The controllability of navigated MLP in dry retina is improved compared to edematous retina. This study validates that pretreatment diagnostic images can be used as basis for navigated MLP after the edema has been resolved.